CONCEPTION ET INSTALLATION D’UN SYSTEME ANTI INCENDIE AVEC EMISSION D’ALARME A DISTANCE DANS LA STATION-SERVICE « MOBIL OIL/KISANGANI ». - LOLEKEONGEMBE, Joseph; LIBENGEMONGAMBO, Dieudonné; BOKUBALIMONGAMBO, Jean Oscar (IJRDO -Journal of Computer Science Engineering, 2023)
Thedesignandinstallationofafirefightingsystemwithremotealarminaservicestationisthebestwaytoprotectworkersandfacilitiesfromexposuretooccupationalhazards.Andyet,itposesenormousproblemsintermsofimplementation,giventhemultipletechnologiesinvolved.Inthisarticle,wetakealookattheessentialstepsinvolvedinbuildingthissystemandthetechnologyused.ThisisthecaseoftheMOBILOIL/Kisanganiservicestation,whichneededtopreventandmanageafirecrisis,thusprotectingpropertyandpeople,andworkinginserenity.Theaimofthisarticleistodefinetheanalyticalandconceptualstagesofananti-firesystembasedonthetechnologyofinstallingmulti-parametersensors(smoke,temperature,flame),andlinkingthemtoacentralizedmodulewhichmanagesallthesedetectorsandtriggers,dependingonthesituation,acertainalarmsignalandactsappropriatelytoeacheventdetected,enablingthisservicestationtohaveasystemadaptedtoitssecurityneedsandwhichisdirectlylinkedtotherestofitsinfrastructure.